2011
DOI: 10.1177/0961203311400112
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of leukocyte CR1 transcript and protein with the pathophysiology and prognosis of systemic lupus erythematosus: A follow-up study

Abstract: Complement Receptor 1 (CR1) is a key complement regulatory protein (CRP) involved in the clearance of immune complexes. Earlier, we reported a marked decline of leukocyte CR1 (L-CR1) transcript and protein in patients with active systemic lupus erythematosus (SLE) and suggested L-CR1 transcript as a putative non-invasive disease marker for SLE. This follow-up study involving 18 patients with active SLE was conducted for further confirmation of the relationship between L-CR1 and SLE. Blood samples from the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
10
1
Order By: Relevance
“…In a similar way to CD21 and CD32, CD35 is also related to some autoimmune diseases [34,35]. It had been shown that soluble recombinant CD35 improves inflammation, demyelination, and severity of clinical disease in a rat model of MS disease [36].…”
Section: Discussionmentioning
confidence: 99%
“…In a similar way to CD21 and CD32, CD35 is also related to some autoimmune diseases [34,35]. It had been shown that soluble recombinant CD35 improves inflammation, demyelination, and severity of clinical disease in a rat model of MS disease [36].…”
Section: Discussionmentioning
confidence: 99%
“…In SLE patients, Arora et al [9] suggested that an increase in the levels of L-CR1 was related to a good prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, case-control and longitudinal studies carried out by us documented the diseaserelated modulation of L-CR1 transcript and protein in SLE [8,9]. Subsequently, the L-CR1 transcript and protein were suggested as potential disease activity markers of SLE [9]. No study of this kind has been carried out for RA and other systemic autoimmune disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In neutrophils from SLE patients, IC downregulates the levels of CR1 transcripts, both directly and indirectly via inhibiting IFN-γ-induced CR1 expression, an example of how lupus activity affects CR1 expression [14]. Nonetheless, higher CR1 expression on SLE patient leukocytes indicates a better prognosis [15], while lower leukocyte MCP expression is associated with lupus remission [16]. These findings not only suggest the pivotal roles of the complement system in the pathogenesis of SLE, but may also potentially provide noninvasive markers for the disease activity.…”
Section: The Role Of the Complement System In Human Slementioning
confidence: 99%